Professional Sports - Aprillia Sumenda; Melky Pangemanan (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Professional sports have become one of the largest industries in the world, with a significant impact on the economy, culture, and society. Professional athletes who make sports activities as a profession, have rights, one of which is to get a decent income.This paper explores various aspects of professional sports, including league structure, media role, and sponsorship influence. Using an analytical approach and empirical data, this study identifies the latest trends in consumer behavior, such as increasing interest in interactive viewing experiences and the use of digital platforms. In addition, this research also discusses the challenges faced by athletes, including mental health problems, injuries, and pressure to perform. This finding provides valuable insight for team managers, marketers, and policy makers in formulating strategies that support the sustainability and growth of professional sports in the future.